Chilean University Students’ Satisfaction With Online Learning During COVID-19 Pandemic: Demonstrating the Two-Layer Methodology - Montero, Rodrigo; Gempp, René; Vargas, Miguel (Frontiers in Psychology, 2022)
Student satisfaction is a crucial determinant of success in online education, but studies on satisfaction with virtual classes during the COVID-19 outbreak are still scarce. This research contributes empirical evidence regarding the determinants of overall satisfaction with online classes and academic performance through the domain satisfaction approach. Additionally, we introduce to the psychological literature the two-layer model, a well-known econometric methodology, to estimate the effect of domain satisfaction while controlling the impact of unobserved individual differences. Our analyses are based on a cross-sectional sample of n=648 Chilean university students (53,4% female) surveyed at the end of the first academic semester of 2021, during the lockdown mandated by the Chilean government due to the COVID-19 pandemic. Results show that satisfaction with the support provided by the university, satisfaction with learning, and satisfaction with the perceived quality of the online classes, significantly explain the 68% of the variance of satisfaction with the virtual classes experience. Furthermore, satisfaction with academic performance is significantly explained by satisfaction with grades, learning, and the perceived quality of the online classes (R2=.65). We also explore heterogeneous effects, separating them by gender and geographic area, and find that domains that systematically impact students' satisfaction with online education are satisfaction with grades, learning, and the quality of classes.